2021
DOI: 10.26508/lsa.202000940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating CRISPR-based prime editing for cancer modeling and CFTR repair in organoids

Abstract: Prime editing is a recently reported genome editing tool using a nickase-cas9 fused to a reverse transcriptase that directly synthesizes the desired edit at the target site. Here, we explore the use of prime editing in human organoids. Common TP53 mutations can be correctly modeled in human adult stem cell–derived colonic organoids with efficiencies up to 25% and up to 97% in hepatocyte organoids. Next, we functionally repaired the cystic fibrosis CFTR-F508del mutation and compared prime editing to CRISPR/Cas9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…Through comprehensive tests and analysis of PE3 activity at endogenous targets, we observed several strengths and weaknesses of this system in hESCs, as follows: (i) PEs are capable of introducing all types of base substitutions at positions as far as 30 bps downstream of the nicking site in hPSCs and showed a trend of activity similar to that seen in other human cell lines such as HEK293T, but in general, prime editing efficiencies are lower in hPSCs than in other cell lines, (ii) Compared to PEs, BEs showed higher base conversion activities but generated bystander edits, whereas PEs provided precise base conversion without bystander edits, (iii) PE3-mediated base conversion is generally accompanied by the generation of indels, which are mainly caused by the combinatory activity of RT and the pegRNA, rather than by the double nicking strategy per se and (iv) WGS results revealed that long term overexpression of PE2 in hESCs did not generate significant frequencies of genome-wide SNVs or indels. Recent studies in organoid model systems showed that prime editing produces higher desired edit/indel ratios than HDR and that base editing is superior to prime editing in terms of editing efficiency ( 32 , 37 ), which is consistent with our conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…Through comprehensive tests and analysis of PE3 activity at endogenous targets, we observed several strengths and weaknesses of this system in hESCs, as follows: (i) PEs are capable of introducing all types of base substitutions at positions as far as 30 bps downstream of the nicking site in hPSCs and showed a trend of activity similar to that seen in other human cell lines such as HEK293T, but in general, prime editing efficiencies are lower in hPSCs than in other cell lines, (ii) Compared to PEs, BEs showed higher base conversion activities but generated bystander edits, whereas PEs provided precise base conversion without bystander edits, (iii) PE3-mediated base conversion is generally accompanied by the generation of indels, which are mainly caused by the combinatory activity of RT and the pegRNA, rather than by the double nicking strategy per se and (iv) WGS results revealed that long term overexpression of PE2 in hESCs did not generate significant frequencies of genome-wide SNVs or indels. Recent studies in organoid model systems showed that prime editing produces higher desired edit/indel ratios than HDR and that base editing is superior to prime editing in terms of editing efficiency ( 32 , 37 ), which is consistent with our conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…The Nobel Prize for Chemistry in 2020 was awarded to Jennifer Doudna and Emmanuelle Charpentier for their discovery of the CRISPR/Cas9 system—the most versatile and commonly used gene editing technique [ 350 , 351 ]. It has been successfully employed in correcting CFTR mutations in translational cell models, such as rectal organoids [ 352 , 353 , 354 ] and airway epithelial progenitor (basal) cells [ 355 , 356 ]. We recently reviewed gene editing in CF and its potential for therapeutic approaches and model generation in detail.…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
“…In addition, frameshift mutations caused by small indels might be rescued by base or prime editing approaches in the future. Collectively, these CRISPR/Cas technologies have, to date, mainly focused on the repair of F508del, PTC mutations and 3849+10kbC>T [ 353 , 354 , 379 ], and can be further expanded to study the repair of most CFTR mutations (reviewed in [ 267 ]). Larger deletions, however, such as the 21kb deletion mutation CFTRdele2,3 cannot be targeted by this type of strategy and will require other corrective means such as gene addition (reviewed in [ 339 ]), super-exon insertion (see [ 356 , 380 ] for examples, although neither super-exon designs include the region deleted in CFTRdele2,3), stimulation of alternative chloride channels or ENaC inhibition (reviewed in [ 381 , 382 ]).…”
Section: Towards the Future: Personalizing Therapies For Pwcfmentioning
confidence: 99%
“…Integrating sequences for transcription factor binding sites and splicing modulators provides control over gene expression, while introducing structural elements or recombinase sites can change DNA conformation and provide a substrate for large-scale engineering 1,2 . For therapeutic opportunities, over 16,000 small deletion variants have been causally linked to disease 3,4 , and could in principle be restored by inserting the missing sequence 5,6 . A prominent example is cystic fibrosis, where 70% of cases are caused by a 3 nt deletion 7,8 .…”
Section: Introductionmentioning
confidence: 99%